2019
DOI: 10.1002/jsfa.9555
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced stability of red‐fleshed apple anthocyanins by copigmentation and encapsulation

Abstract: BACKGROUND Red‐fleshed apples are a great source of natural colorants and functional food ingredients because of their high anthocyanin content. Generally, anthocyanins are highly unstable after extraction, which limits their wide applications in the food and pharmaceutical industries. This study was aimed at investigating the effects of combining copigmentation with encapsulation on the stability of anthocyanins from red‐fleshed apples. In this study, red‐fleshed apple anthocyanins were copigmented with caffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 57 publications
(106 reference statements)
1
15
0
Order By: Relevance
“…The kinetic studies confirmed that the degradation rate of anthocyanin was decreased in the presence of SF-AG and CSG, and this is while CSG had better performance in stabilizing the anthocyanin in all temperatures. Recently, anthocyanin was successfully stabilized using gellan gum, Arabic gum, and Xanthan gum anthocyanins (Cai et al, 2019;Teleszko et al, 2019;Xue et al, 2019). For instance, using high acyl and low acyl gellan gum, the halflife of anthocyanin at 90 • C was increased from 135 min to 274 min and 212 min, respectively (Xu et al, 2019).…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetic studies confirmed that the degradation rate of anthocyanin was decreased in the presence of SF-AG and CSG, and this is while CSG had better performance in stabilizing the anthocyanin in all temperatures. Recently, anthocyanin was successfully stabilized using gellan gum, Arabic gum, and Xanthan gum anthocyanins (Cai et al, 2019;Teleszko et al, 2019;Xue et al, 2019). For instance, using high acyl and low acyl gellan gum, the halflife of anthocyanin at 90 • C was increased from 135 min to 274 min and 212 min, respectively (Xu et al, 2019).…”
Section: 2mentioning
confidence: 99%
“…The heat resistance of anthocyanin has been improved using chitosan, metal cations, and pectin because of molecular interactions of polysaccharides and anthocyanin (Santos et al, 2019). Additionally, sodium alginate, xanthan gum, and guar gum were successfully used to stabilize anthocyanins (Cai et al, 2019;Teleszko et al, 2019;Xue et al, 2019;Zhang et al, 2020). Xue-Jiang investigated the effect of gellan gum on the thermal stability of anthocyanins from purple potato and discovered that the high-acyl gellan gum had stronger binding interaction with anthocyanin according to molecular dynamics simulation, which is because of its higher functionality (Xu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from biopolymers, phenolic compounds are also incorporated in the spray/freeze-dried microparticles. For example, caffeic acid has been used to copigment redfleshed apple anthocyanins at the molar ratio of 30:1, which is then mixed with a matrix of gum arabic and maltodextrin for spray/freeze-drying (Xue et al, 2019). By this means, the red color of spray-dried microparticles is significantly intensified, as well as the degradation of anthocyanin is retarded even with exposure to heat at 80 • C for 2 hr and natural light for 12 days.…”
Section: Spray/freeze-dryingcopigmentationmentioning
confidence: 99%
“…This also appears in foods having anthocyanins as natural colorants (Trouillas et al, 2016; Cortez et al, 2017). Moreover, anthocyanins present an inherent nature of associating with copigments (Escribano-Bailon and Santos-Buelga, 2012; Trouillas et al, 2016; Cortez et al, 2017; Qian et al, 2017; Gras et al, 2018), e.g., colorless polyphenols, which allows to maintain the flavylium cation state and to stabilize the color (Boulton, 2001; Gómez-Míguez et al, 2006; Malaj et al, 2013; Trouillas et al, 2016; Qian et al, 2017; Ertan et al, 2018; Gras et al, 2018; He et al, 2018; Tan et al, 2018; You et al, 2018; Fan et al, 2019; Klisurova et al, 2019; Sun et al, 2019; Xue et al, 2019; Xu et al, 2019). This phenomenon is known as copigmentation effect.…”
Section: Introductionmentioning
confidence: 99%
“…However, a onefold experimental selection can imply high cost. That may be the reason why often in the experiments a small number of copigments is taken into account (Boulton, 2001; Gómez-Míguez et al, 2006; Kunsági-Máté et al, 2006; Lambert et al, 2011; Kalisz et al, 2013; Malaj et al, 2013; Teixeira et al, 2013; Xu et al, 2015, 2019; Zhang et al, 2015; Ertan et al, 2018; He et al, 2018; Tan et al, 2018; You et al, 2018; Fan et al, 2019; Klisurova et al, 2019; Sun et al, 2019; Xue et al, 2019).…”
Section: Introductionmentioning
confidence: 99%